Evaluasi Tebal Lapis Tambah Perkerasan Lentur Menggunakan Metode Bina Marga (Pd T-05-2005-B) dan Asphalt Institute (MS-17) (Studi Kasus Jalan Yogyakarta- Bantul) - Ilham Haris; Anita Rahmawati (Universitas Muhammadiyah Yogyakarta, 2013)
The overlay is the addition of pavement layer thickness which is placed on the existing pavement construction to increase the strength and to serve the planned traffic during the specified period. This research is a case study conducted in Yogyakarta-Batas Kota Bantul road using Bina Marga and Asphalt Institute method. Although a new highway is upgraded, it is possible that the road construction will be damaged in a relatively short time. With this consideration, it is necessary to evaluate the thickness of pavement overlay. The length of the evaluated road segment was divided into three (3) sections, namely Segment I (Sta 4+000 - Sta 5+800), Segment II (Sta 6+000 - Sta 7+800) and Segment III (Sta 8+000 - Sta 10+320) to get the pavement thickness uniformity level. Based on the results of the analysis with the Bina Marga method (Pd T-05-2005-B), the thickness of the layers was added for segment I (6.942 cm), segment II (6.618 cm), and segment III (6.055 cm). While in the calculation using Asphalt Institute (MS-17) method, it was obtained that there was additional layer thickness 3.556 cm in segment I, 3.048 cm in segment II, and 2.790 cm segment III. The result of overlay thickness correction of Bina Marga method using AASHTO equivalent shows the number of 2.794 cm segment I, 2.470 cm in segment II, and 1.907 cm in segment III.